Content and Language Integrated Learning in Teaching English as Second Language: A Systematic Review of Empirically Based Articles - Lailiyah, Malikhatul (D3 English Program Universitas Merdeka Malang, 2016)
This article provides a systematic review of the literature pertaining to the implication of Content and Language Integrated Learning (CLIL) as learning strategies in the education setting. The purpose of this systematic review was to examine existing research related to CLIL, including qualitative, quantitative, and mix-method research. The criteria used to select articles included in this review were: (a) only peer-reviewed article available on ERIC database, (b)the most recently articles that published during the time period 2013-2015, (c) their relevance to the implementation of CLIL in English as Second Language. Five articles that meet the criteria were undertaken in this research to show the application of CLIL in the teaching of English as Second Language. Keywords:Learning strategies, Content and Language Integrated Learning (CLIL), Empirically Research